AFGHANISTAN IN THE GRIP OF THE TALIBAN: A CRITICAL DISCOURSE ANALYSIS OF NEWS IN ARABIC ONLINE MEDIA - Kamal Yusuf; Siti Ismu Wahyul Karimah; Syifauddin Haikal Khan; Wardah Fitrotul Maula Falabiba (International Conference on Social and Islamic Studies, 2021)
News on online media portals has advantages over conventional media in constructing realityand influencing readers. This study aims to analyze the coverage of the case of Afghanistanunder the new Taliban government on BBC Arabic online media with a critical discourseanalysis approach. Furthermore, this article attempts to reveal the elements of the textstructure, analysis of social cognition, and social analysis of the news discourse. This studyuses a descriptive qualitative method with a critical discourse analysis approach of Van Dijk'smodel. The results of this study indicate that the news on BBC Arabic about the collection ofbillions of dollars by the United Nations for humanitarian assistance in Afghanistan, in theview of Van Dijk's critical discourse analysis model can be divided into three levels, namely:first, analysis of text structure (context), in In the structure of this text, there are differences inthe meaning of the news titles raised by BBC Arabic. Second, analysis of social cognition, bylooking at the schemes that play a role in reporting on BBC Arabic, namely the event schemeand the person scheme. Third, analysis of social context, which explores two elements foundin the text, namely the practice of power and access to influence discourse.